Association between Habitual Diet and the Postprandial Glucose Response—An Enable Study. Issue 16 (1st July 2022) - Reik, Anna; Brandl, Beate; Schauberger, Gunther; Wawro, Nina; Linseisen, Jakob; Skurk, Thomas; Volkert, Dorothee; Hauner, Hans; Holzapfel, Christina
Abstract : Scope: It is inconclusive which factors influence inter‐individual variations of postprandial glucose response (PPGR). This study investigates whether the habitual diet is associated with PPGR. Methods and results: Data from healthy adults (young adults with 18–25 years, middle‐aged adults with 40–65 years, and older adults with 75–85 years) is collected at baseline and during an oral glucose tolerance test (OGTT) collected. Habitual diet is assessed by a food frequency questionnaire and two 24‐h food lists. Associations between habitual diet and glucose incremental area under the curve (iAUCmin ) are examined by regression models. The intake of cereals and cereal products is negatively associated with glucose iAUCmin ( p  = 0.002) in the total cohort ( N  = 459, 50% women, 55 ± 21 years, BMI 26 ± 5 kg m − 2 ). Up to 9% of the variance in the glycemic response is explained by the respective dietary parameters identified in the models of the specific age groups. Conclusion: There are age‐specific diet‐related effects on PPGR. The usual intake of cereals and cereal products seems to play a greater role in PPGR in more than one age group. Further research is needed, to establish how diet can be optimized based on age and PPGR. Abstract : It is unclear which factors influence the variability of postprandial metabolism after the intake of standardized meals. This study investigates whether the habitual diet is associated with postprandial glucose response (PPGR) after an oral glucose tolerance test. Carbohydrate intake and the intake of cereals and cereal products are observed to be associated with PPGR. Furthermore, there are age‐specific associations with PPGR.